2019
DOI: 10.1155/2019/6071308
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomes Derived-miR-146a from Systemic Lupus Erythematosus Patients Regulates Senescence of Mesenchymal Stem Cells

Abstract: The senescence of mesenchymal stem cells (MSCs) plays a crucial role in the development and progression of systemic lupus erythematosus (SLE). Exosomes, small spherical bilayer proteolipid vesicles, contribute to the communication between various cells and their microenvironment by transferring information via their cargo, including the proteins, lipids, and RNAs. While exosomal miRNAs participate in various biological activities, correlations of circulating exosomes with senescent signs of BM-MSCs remain uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Nevertheless, there is still a concern that using a single miRNA/exomiR marker in the circulatory system for predicting a particular disease may incur a potential problem of non-specificity. For example, it has been shown recently that the level of serum exosomal miR-146a-5p declined significantly in systemic lupus erythematosus patients compared with healthy controls [43]. Accordingly, the use of a combination of multiple miRNA/exomiR signatures may improve diagnostic specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is still a concern that using a single miRNA/exomiR marker in the circulatory system for predicting a particular disease may incur a potential problem of non-specificity. For example, it has been shown recently that the level of serum exosomal miR-146a-5p declined significantly in systemic lupus erythematosus patients compared with healthy controls [43]. Accordingly, the use of a combination of multiple miRNA/exomiR signatures may improve diagnostic specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The level of miR-146a contained within exosomes in the urine of lupus patients was significantly higher than that outside of exosomes. In contrast, miR-146a levels in serum exosomes were significantly lower in SLE patients than in HCs ( 59 ). Of all miRNAs, miR-146a can significantly distinguish active LN from inactive LN and is related to inflammation and fibrosis of the kidney ( 74 ).…”
Section: The Role Of Evs In Slementioning
confidence: 89%
“…In addition, miR-146a may be upregulated by chemokines as well as proinflammatory cytokines and leads to anemia in SLE patients ( 82 ). MSCs can internalize exosomes with miR-146a and target TRAF6/NF- κ B signaling, leading to the senescence of MSCs ( 59 ). The senescence of MSCs may be related to the disease activity and pathological process of SLE ( 83 , 84 ).…”
Section: The Role Of Evs In Slementioning
confidence: 99%
“…Moreover, it was shown that these increased EVs in the plasma of active SLE patients induced ROS production and degranulation in neutrophils 187 , activated pDCs to secrete IFN-α via TLR7 188 , or contributed to MSC senescence in SLE 189 . The elevated EVs and their immune complexes in SLE patients also promoted secondary leukocyte infiltration by regulating vascular remodeling and chemokine secretion 16 .…”
Section: Ev Involvement In the Pathophysiology Of Inflammatory Skin Dmentioning
confidence: 99%